Contribution of different relapse phenotypes to disability in multiple sclerosis. (February 2017) - Stewart, Tamasine; Spelman, Tim; Havrdova, Eva; Horakova, Dana; Trojano, Maria; Izquierdo, Guillermo; Duquette, Pierre; Girard, Marc; Prat, Alexandre; Lugaresi, Alessandra; Grand'Maison, Francois; Grammond, Pierre; et al.
Objective: This study evaluated the effect of relapse phenotype on disability accumulation in multiple sclerosis. Methods: Analysis of prospectively collected data was conducted in 19, 504 patients with relapse-onset multiple sclerosis and minimum 1-year prospective follow-up from the MSBase cohort study. Multivariable linear regression models assessed associations between relapse incidence, phenotype and changes in disability (quantified with Expanded Disability Status Scale and its Functional System scores). Sensitivity analyses were conducted. Results: In 34, 858 relapses recorded during 136, 462 patient-years (median follow-up 5.9 years), higher relapse incidence was associated with greater disability accumulation (β = 0.16, p < 0.001). Relapses of all phenotypes promoted disability accumulation, with the most pronounced increase associated with pyramidal (β = 0.27 (0.25–0.29)), cerebellar (β = 0.35 (0.30–0.39)) and bowel/bladder (β = 0.42 (0.35–0.49)) phenotypes (mean (95% confidence interval)). Higher incidence of each relapse phenotype was associated with an increase in disability in the corresponding neurological domain, as well as anatomically related domains. Conclusion: Relapses are associated with accumulation of neurological disability. Relapses in pyramidal, cerebellar and bowel/bladder systems have the greatest association with disability change. Therefore, prevention of these relapses is an important objective of disease-modifying therapy. The differential impact of relapse phenotypes on disability outcomes could influence management of treatment failure in multiple sclerosis.